Shelby Foote : novelist and historian - Phillips, Robert L., Jr. (Robert LeRoy), 1940- (University Press of Mississippi, 2006)
Called the greatest Civil War historian, Shelby Foote began his career as a novelist whose powerful works of fiction rose out of his closeness to life and culture in his native region, the Mississippi Delta country. Later in his career he transformed modern historical prose by his keen sense of the novel. His artistic distance from the elements of regionalism that lie at the heart both of his novels and of his history writing gives his prose great narrative force. This perceptive study fills the genuine need for a sound critical appreciation of Foote the novelist. After he appeared as a sage commentator in the PBS series The Civil War, the popular acclaim that catapulted Shelby Foote the historian to even greater eminence as an American oracle renewed much deserved interest in his novels and in critically rich assessments such as this one.